DRIVING FACTORS OF CHANGE AT PESANTREN TEBUIRENG - Subhi, Imam; Fahad, M.; Putriyani, Putriyani (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Pesantren Tebuireng is one of the large and old Pesantren in Jombang Regency, East Java Province, which has succeeded in making big and fast changes in various vital and strategic aspects, so that the great name of Tebuireng keeps existing and contributing positively to national development. This change does not happen by itself but there are a lot factors encouraging it. Therefore, this study aims to examine those factors which are driving the change at Pesantren Tebuireng. The form of this research is qualitative with a case study approach that examines the phenomenon of change by exploring the data through observation, interviews, and documentary studies. The result of this study is that the factors, driving the change at Pesantren Tebuireng, are grouped into two, namely the first is external factors which include competition in the quality of education, dynamic community demands, and alumni encouragement; The second is internal factors which include organizational structure that is not comprehensive, organizational culture, and low quality of human resources yet.